Respuesta :
Answer:
[tex]7x - 10 - x = 2x + 26[/tex]
Taking like terms ( i.e. terms with same variables ) to left side and constant terms ( i.e. simple numbers ) to right side . .
[tex]⇢7x - x - 2x = 26 + 10[/tex]
[tex]⇢6x - 2x = 36[/tex]
[tex]⇢4x = 36[/tex]
[tex]⇢x = \frac{36}{4} [/tex]
[tex]⇢ \boxed{x = 9}[/tex]
Answer:
x = 9
Step-by-step explanation:
#1) Simplify each side.
- 7x - 10 - x = 2x + 26
- 6x - 10 = 2x + 26
#2) Bring x terms to the left side and numbers to the other side.
- 6x - 2x = 26 + 10
- 4x = 36
#3) Divide both sides by 4.
- 4x/4 = 36/4
- x = 9